Q-switched Thulium-doped fiber laser at 1860 nm and 1930 nm using a Holmium-doped fiber as an amplified spontaneous emission filter. (March 2020) - Sharbirin, A.S.; Ahmad, H.; Ismail, M.F.
Highlights: The laser cavity can generate a laser at 1930 nm and 1860 nm. The cavity employs a Holmium-doped fiber to suppress the amplified spontaneous emission of the Thulium ions. Passive Q-switching for both wavelengths is achieved using the same Molybdenum Tungsten Disulfide (MoWS2 ) film. The laser at 1860 nm generates a maximum repetition rate of 48.9 kHz as well as narrowest pulse width of 2.3 µs. Abstract: This work demonstrates an all fiber, passively Q-switched Thulium-doped fiber (TDF) laser with a center operating wavelength at 1860 nm and 1930 nm. The laser initially generates an output at 1930 nm which is then shifted to 1860 nm by integrating a Holmium-doped fiber (HDF) into the cavity to serve as an amplified spontaneous emission filter. Q-switching operation is achieved using a molybdenum tungsten disulfide or MoWS2 thin film acting as a passive optical modulator. At 1930 nm, the generated Q-switched laser has a high repetition rate of 66.3 kHz and a narrow pulse width of 2.1 µs. After the Holmium-filter is employed, the wavelength shifts to 1860 nm while still retaining a modulated output with a maximum repetition rate of 48.9 kHz as well as narrowest pulse width of 2.3 µs. This work demonstrates the use of the absorption characteristics of HDF to access the shorter wavelength region of the TDF.